Effect of Water Spinach Spacing and Planting Time on Chili Growth in Chili-Water Spinach Intercropping - Rohmatin Agustina; Tutus Rahmawati; Setyo Budi; Rahmad Jumadi (Institut Pertanian Bogor, 2025)
Chili is one of the horticulture crops with the highest commercial value. Farmers can cultivate chili in intercropping systems with water spinach plants as a land-saving alternative. The purpose of this study was to determine the optimal chili planting distance and water spinach planting timing for increasing chili plant growth in chili-water spinach intercropping cultivation. A factorial randomized group design was adopted in this study. The first consideration was the spacing between the chili plants, which measure 50´70 cm and 50´50 cm, respectively. The second aspect was to plant water spinach at the same time as chili, one week after planting (1 WAP) chili, and 2 WAP chili. The findings indicate that optimum spacing and planting time for water spinach can improve the growth of chili plants. When chili plants were spaced 50´70 cm apart, their height and number of leaves increased dramatically. When compared to other treatments, the planting time of water spinach 1-2 WAP chili resulted in significantly higher plant height and number of leaves. All growth variables examined were significantly influenced by the interaction of 50´70 cm and water spinach planting time 2 weeks after chili planting. Keywords: chili, intercropping, planting distance, planting time, water spinach